COMPARATIVE ANALYSIS OF MARRIAGE DISPENSATION ARRANGEMENTS IN LEGISLATION IN INDONESIA - Bima, Muhammad Rinaldy (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This thesis aims to determine the age limit for marriage as regulated in Law No. 16 of 2019. The law regulates the minimum age for marriage, which is 19 (nineteen) years for both men and women. In addition, this thesis also examines the implementation of the new Marriage Law in the city of Makassar and the factors that cause underage marriages in the city of Makassar. This research uses empirical legal research (non-doctrinal legal research), which is a legal research method that focuses attention on the legal reality in society. The conclusion is that the number of underage marriages in the city of Makassar is still relatively high both before and after the enactment of Law No. 16 of 2019 concerning marriage in October 2019. The percentage of underage marriages in the Makassar City Religious Court obtained the following data: there were 70 cases of underage marriages in 2017, 82 cases in 2018, 57 cases in 2020, and there were 44 cases in 2021. In addition, based on the results of research, several factors cause underage marriages in Makassar City, including education factors, accidental marriage (pregnancy out of wedlock), low level of education, and economic factors. The recommendation of this research is for the community because many requests for dispensation from marriage are motivated by the social environment, one of which is because of association. Therefore, it is necessary to give religious understanding from an early age to minimize the occurrence of things that are not good.